Fibonacci, Lucas Numbers with Daul Bicomplex Numbers (Journal of Informatics and Mathematical Sciences, 2018)
Recently, the authors give some results about Fibonacci and Lucas numbers. In this present paper, our object introduce a detailed study of a new generation of dual bicomplex Fibonacci numbers. We define new dual vector which is called dual Fibonacci vector. We give properties of dual Fibonacci vector to expert in geometry and then we introduce some formulas, facts and properties about dual bicomplex Fibonacci numbers and variety of geometric and algebraic properties which are not generally known.
Keywords: Dual bicomplex Fibonacci numbers; Dual Fibonacci numbers; Dual Lucas numbers; Dual Fibonacci vector